Development of Intelligent Prosthetic Ankle Joint: 1st Report, Development of Linear-Type MR-Fluid Brake - FURUSHO, Junji; NAKAGAWA, Akio; TSUDA, Takeshi; MORIMOTO, Shoji; TAKESUE, Naoyuki; NAKAGAKI, Satoko (Transactions of the Japan Society of Mechanical Engineers Series C, 2004)
We aim to develop an intelligent prosthetic foot that has the braking system of ankle joint. Magnetorheological (MR) fluids is material that changes their rheological behavior by an applied magnetic field. A brake using MR fluid can change the braking force according to the strength of applied magnetic field. In this paper, we develop the linear brake using MR fluid for the intelligent prosthetic foot, and carry out the virtual walking experiment by the use of that brake.